Fuzzy Model on Online Treatment Analysis for COVID-19 - Dolorosa, E. Anita; Pathinathan, T. (Communications in Mathematics and Applications, 2021)
The purpose of this paper is to introduce a fuzzy model for patients suffering from COVID-19. We have defined primary, normal and abnormal infections based on the symptoms of the patients. Fuzzy numbers and Reverse order fuzzy numbers have been used to identify the stages of each patient. These models may help the doctors for online treatment of patients.